2021
DOI: 10.3389/fpubh.2021.784958
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Risk Factors for Alzheimer's Disease in Racial/Ethnic Minority Populations in the U.S.: A Scoping Review

Abstract: Objectives: As the United States (U.S.) population rapidly ages, the incidence of Alzheimer's Disease and Related Dementias (ADRDs) is rising, with racial/ethnic minorities affected at disproportionate rates. Much research has been undertaken to test, sequence, and analyze genetic risk factors for ADRDs in Caucasian populations, but comparatively little has been done with racial/ethnic minority populations. We conducted a scoping review to examine the nature and extent of the research that has been published a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 116 publications
0
15
0
Order By: Relevance
“…APOE ε3 is the most common allele 12 and is neutral in relation to risk for AD dementia 11 . APOE ε4 is associated with a higher risk of AD dementia 13 (mostly in non‐Hispanic White [NHW] populations 14 ), whereas APOE ε2 is associated with a lower risk of AD dementia 15 . Studies suggest that there are sex differences in the effects of APOE ε4 on AD risk, such that women with APOE ε4 are disproportionately vulnerable to cognitive impairment 16 and AD 15 compared to their counterpart men.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…APOE ε3 is the most common allele 12 and is neutral in relation to risk for AD dementia 11 . APOE ε4 is associated with a higher risk of AD dementia 13 (mostly in non‐Hispanic White [NHW] populations 14 ), whereas APOE ε2 is associated with a lower risk of AD dementia 15 . Studies suggest that there are sex differences in the effects of APOE ε4 on AD risk, such that women with APOE ε4 are disproportionately vulnerable to cognitive impairment 16 and AD 15 compared to their counterpart men.…”
Section: Introductionmentioning
confidence: 99%
“…[NHW] populations 14 ), whereas APOE ε2 is associated with a lower risk of AD dementia. 15 Studies suggest that there are sex differences in the effects of APOE ε4 on AD risk, such that women with APOE ε4 are disproportionately vulnerable to cognitive impairment 16 and AD 15 compared to their counterpart men.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we summarized the risk factors for AD/ADRD by reviewing existing meta-analyses and review articles on risk and preventive factors for AD/ADRD. Compared with the previous studies [19][20][21][22][23][24], our work provides a updated review of recent publications on AD/ADRD-related risk factors. Drawing from this literature review and identified AD/ADRD factors, we explored the accessibility of these risk and preventive factors in both structured and unstructured EHR data.…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer’s disease (AD) is the most common cause of dementia accounting for 60-80% of dementia cases. 4 The common risk factors for AD dementia include age, genetics, family history, race/ethnicity, 5 low education, excessive alcohol consumption, smoking, obesity, hypertension, hearing impairment, depression, physical inactivity, diabetes, poor heart health, and traumatic brain injury. 6, 7 Addressing preventable risk factors (e.g.…”
Section: Introductionmentioning
confidence: 99%